Kombinasi Glucomannan Hydrolysates (Gmh) Dan Antibiotik Metronidazole Berpengaruh Terhadap Kadar Sitokin Il-23 Pada Bacterial Vaginosis Wanita Usia Subur - Purwanti, Anik Sri; Sumarno, Sumarno; Rahardjo, Bambang; Winasih, Sri; Poeranto, Sri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Woman’s reproductive tract often has problems, especially in women of childbearing age. One of them is Bacterial Vaginosis is a clinical condition that occurs a lot. BV infection is a polymicrobial infection caused by a decrease in the amount of Lactobaclilus with anaerobic bacteria that increases excessively. Alternative treatment for BV is given by using the results hydrolysates of konjac plant extracted in dosage forms Glucomannan Hydrolysates (GMH) containing glucose and mannose prebiotic which can support the growth development of Lactobacillus in the vaginal mucosa. This study was to determine the effect of Glucomannan Hydrolisates (GMH) + Metronidazole on levels of IL 23 cytokines in BV of reproductive age women. The method of this study used the True Experimental design with the type of research The randomized pretest-posttest was in vivo. The subjects selected in this study design used Randomized techniques. A sample of 7 people WUS with BV given GMH 300mg + Metronidazole 1000 mg for 9 days of use, To assess the levels of cytokine IL 23 using the ELISA method. Data analysis using a ratio scale was analyzed using the metric statistical test, normality test using Shapiro-Wilk test and comparative test using Repeated Measure ANOVA. The overall results of the analysis showed that the combination of GMH and Antibiotics Metronidazole could significantly increase the levels of cytokine IL 23 compared to other therapies to treat bacterial vaginosis in women of childbearing age